Statistical analysis of a weighting scheme for asteroid observation astrometric errors taking into consideration the classification of the observed asteroids - Stronati, Nicolò; Faggioli, Laura; Micheli, Marco; Ceccaroni, Marta (International Astronautical Federation (IAF), 2022)
Observations of asteroids and other near-Earth objects are of great importance for planetary defence activities, the purpose of which is to determine their positions in space and the probabilities of Earth impacts, as well as developing strategies to mitigate this risk. In this framework, having precise observations is important to describe accurately the orbits of near-Earth asteroids. However, given a general absence of a-priori uncertainty information, the single observations are given proper weights that reflect the accuracy expected by the observers who perform the observations. The weights are calculated for each observer on the base of statistical analysis of systematic and random errors and providing them with an accurate definition is necessary if the magnitude of the error of a single observation is to be correctly estimated. In this paper a statistical analysis on the residuals of the astrometric data provided by the major surveys is presented introducing a dynamic classification of observed asteroids. The observations are thus subdivided between those relative to Near Earth and Main Belt Asteroids and the quality of the data for each station is studied focussing on this classification. The results show that most of the considered stations have the same quality regardless of the measured object, while four of them show a dependency on this factor.